Manajemen Pengarsipan Data Personal Karyawan Pada PT Pupuk Iskandar Muda Kabupaten Aceh Utara - Sutriani Sutriani; Chalirafi Chalirafi; Ristati Ristati (Jurnal Visioner & Strategis, 2021)
This research contains procedures for archiving employee personal data at PT Pupuk Iskandar Muda. The archive must be managed with proper procedures because it has an important role as a source of information. Sources of data are obtained based on sources, documents, and archives. Based on the observations made by the author, the procedure for archiving employee personal data at PT Pupuk Iskandar Muda is divided into two parts, namely manual archiving and electronic archiving, to facilitate the organization and retrieval of archives. The obstacle faced is the lack of archive storage facilities and infrastructure, both manual and electronic storage, so it needs to be maximized so that the employee archives that have been stored are not easily damaged or lost.